Exon Deletion Pattern in Duchene Muscular Dystrophy in North West of Iran - BARZEGAR, Mohammad; HABIBI, Parinaz; Mortaza BONYADY, Mortaza; TOPCHIZADEH, Vahideh; SHIVA*, Shadi (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Barzegar M, Habibi P, Bonyady M, Topchizadeh V, Shiva Sh. Exon Deletion Pattern in Duchene Muscular Dystrophy in North West of Iran. Iran J Child Neurol. 2015 Winter; 9(1): 42-48. Abstract Objective Duchene and Becker Muscular Dystrophy (DMD/ BMD) are x-linked disorders that both are the result of heterogeneous mutations in the dystrophin gene. The frequency and distribution of dystrophin gene deletions in DMD/ BMD patients show different patterns among different populations. This study investigates the deletion rate, type, and distribution of this gene in the Azeri Turk population of North West Iran. Materials &Methods In this study, 110 patients with DMD/ BMD were studied for intragenic deletions in 24 exons and promoter regions of dystrophin genes by using multiplex PCR. Results Deletions were detected in 63 (57.3%) patients, and around 83% localized in the mid-distal hotspot of the gene (on exons 44–52), 21 cases (33.3 %) with singleexon deletions, and 42 cases (66.6%) with multi-exonic deletions. The most frequent deleted exons were exon 50 (15 %) and exon 49 (14%). No deletion was detected in exon 3. Conclusion This study suggests that the frequency and pattern of dystrophin gene deletions in DMD/ BMD in the Azeri Turk population of North West Iran occur in the same pattern when compared with other ethnic groups. References Emery AE. Clinical and molecular studies in Duchenne muscular dystrophy. Prog Clin Biol Res 1989; 306:15-28. Moser H. Duchenne muscular dystrophy: pathogenic aspects and genetic prevention. Hum Genet 1984; 66(1):17-40. Emery AE. Population Frequencies of inherited neuromuscular diseases: a world survey Neuromuscul Disord 1991; I (I):19-29. Bushby KM, Thmabyayah M, Gardner M D. Prevalence and incidence of Becker muscular dystrophy. Lancet 1991; 337(8748):1022-1024. Koenig M, Hoffman EP, Bertelosn CJ, Monaco AP, Feener C, Kunkel LM. Complete cloning of the Duchenne muscular dystrophy (DMD) DNA and preliminary genomic organization of the DMD gene in normal and affected individuals. Cell 1987; 50:509-517. Den Dunnen JT, Grootscholten PM, Bakker E, Blonden LA, Ginjaa rHB, Wapenaar MC, Van Paasen HM, Van Broeckhoven C, Pearson PL, Van Ommen GJ. Topography of the Duchenne muscular dystrophy (DMD) gen. Am J Hum Gennet 1989; 45(6):835-847. Monaco AP, Bertlson CJ, Liechti-Gallati S, Moser H, Kunkel L.M. An explanation for the phenotypic differences between patients bearing partial deletions of the DMD locus.Genomics1988; 2:90-95. Forrest SM, Cross GS, Flint T, Speer A, Robson KJ, Davies KE. Further studies of gene deletions that cause Duchenne and Becker muscular dystrophies. Genomics 1988; 2(2):109-114. Hux Y, Ray PN, Murphy EG, Thompson MV, Worton RG. Duplicational mutation at the Duchenne muscular dystrophy locus: its frequency, distribution, origin, and phenotype-genotype correlation. Am J Hum Genet 1990; 46:682-695. Roberts RG, Bobrow M, Bentley DR. Point mutations in the dystrophin gene. Proc Nat Acad Sci USA1992; 89(6):2331-2335. Mukherjee M, Chaturvedi LS, Srivastava S, Mittal RD, Mital B. Denovo mutations in sporadic deletional Duchenne muscular dystrophy (DMD) cases. Exp Mol Med 2003; 35(2):113-117. Brooke MG, Griggs RC, Mendell GR, Fenichel GM, Shumate JB, Pellegrino RJ. Clinical Trial in Duchenne Dystrophy. Design of the protocol. Muscle& Nerve 1981; 4: 186-197. Beggs AH. Multiplex PCR for identifying dystrophin gene deletions In: Dracopoli NC, Haines JL, Korf BR, Moir DT, Morton CC, Seidman CE, et al. Current protocol in human genetics. 1st ed. New York, John Wiley & Sons 2000;unit 9.3 Prior TW, Bridgeman SJ. Experience and strategy for the molecular testing of Duchenne muscular dystrophy, J Mol Diagn 2005; 7(3):317-26. Chamberlain JS, Gibbs RA, Ranier JE, Nguyen PN, Caskey CT. Deletion screening of the Duchenne Muscular Dystrophy locus via multiplex DNA amplification. Nucleic Acids Res1988;16(23):11141-56. Beggs AH, Kunkel LM. Improved diagnosis of Duchenne/ Becker muscular dystrophy. J Clin Invest1990; 85:613-619. Lai Kent KS ,Ivan FM, Tony MF, Lydia YL et al. Detecting exon deletions and duplications of DMD gene using Multiple Ligation dependent Probe Amplification (MLPA).Clinical Biochemistry (2006);39:367-372. Haider MZ, Bastaki L, Habib Y, Moosa A. Screening 25 dystrophin gene exons for deletions in Arab children with duchenne muscular dystrophy. Hum Hered. 1998; 48; 61- 66. Hassan MJ, Mahmood S, Ali G, Bibi Nm, Washeed I, Rafiq MA, Ansar M, Ahmad W, et al. Intragenic deletions in the dystrophin gene in 211 Pakistani Duchenne muscular dystrophy patients. Pediatr Int 2008; 50: 162- 166. Sbiti A, El Kerch F, Sefiani A. Analysis of dystrophin gene deletions by multiplex PCR in Moroccan patients. J Biomed biotechnol 2002; 2:158-160. Akbari M et al. Molecular diagnosis of Duchenne/Becker Muscular Dystrophy: Analysis of exon deletion and carrier detection. Yakhte Medical Journal 2010; 2(3):421- 428. Galehdari H, Pedram M, Momen AA, Mohammadian GH R, Taherian E. Study of exon deletion in the dystrophin gene in individuals being diagnosed with Duchenne Muscular Dystrophy in Ahvaz. Sci Med J 2011; 10(4):373-382. Jabbarpourbonyadi M, Barzgar M, Ayremlo H, Khandagi R, Esmaiili M. Screening and genetic diagnosis of Duchenne-Becker muscular dystrophy in East Azerbaijan by multiplex-PCR. Medical Journal of Tabriz University of Medical Sciences and health services2006; 28(1):33- 39. Ulgenalp A, Giray O, Bora E, Hizli T, Kurul S, Sagin- Saylam G, Karasoy H, Uran N, Dizdarer G, Tutuncuoglu S, Drink E, Ozkinay F, Ercal D. Deletion analysis and clinical correlations in patients with Xp21 linked muscular dystrophy, The Turkish journal of pediatrics 2004;46:333-338. Onengut S, Kavaslar GN, Battaloglu E, Serdaroglu P, Deymeer F, Ozdemir F, Ozdemir C. Calafell F, Tolun A. Deletion pattern in the dystrophin gene in Turks and a comparison with Europeans and Indians. Ann Hum Genet 2000; 64:33-40. Baumbach J, Chamberlain JS, Ward PA, Farwell NJ, Caskey CT. Molecular and clinical correlations of deletions leading to Duchenne and Becker muscular dystrophies. Neurology 1989; 39(4):465-474. Koenig M1, Beggs AH, Moyer M, Scherpf S, Heindrich K, Bettecken T, Meng G, Müller CR, Lindlöf M, Kaariainen H, et al. The molecular basis for Duchenne versus Becker muscular dystrophy: correlation of severity with type of deletion. Am J Hum Genet 1989; 45(4):498-506. Helderman-van den E, Straathof CSM, Aartsma A, Dendunnen JT, Verbist BM, Bakker E, Verschuuren JJJM, Ginjaar HB. Becker muscular dystrophy patients with deletions around exon 51; a promising outlook for exon skipping therapy in Duchenne patients. Neuromuscular disorders 2010; 20:251-254. Artsma-Rus A, Fokkema I, Verschuuren J, Ginjaar L, Deutekom GV, Ommen GJV et al. Theoretic applicability of antisense-mediated exon skipping for duchenne muscular dystrophy mutations. hummutat 2009; 30:293-9. Van Deutekom JC, Janson AA, Ginjaar LB, Frankhuizen WS, Artsma-Rus A, Bremmer-Bout Mattie et al. Local dystrophin restoration with antisense oligonucleotide PRO051. N Engl Med 2007; 357:2677-86.